In vivo metabolism of 4-fluorobenzoic acid [(5-nitro-2-furanyl)methylene] hydrazide in rats - (:unkn) unknown (Editions Medecine et Hygiene, 2000)
It is known that substituted hydrazide hydrazone derivatives have several biological and pharmacological activities; there is limited literature on the metabolism of hydrazide hydrazones in rats. In our previous study, 4-fluorobenzoic acid [(5-nitro-2-furanyl)methylene]hydrazide (S) was found active against Staphylococcus aureus ATCC 29213. Therefore, we planned to study the in vivo metabolism of S in rats. The substrate was administered in doses of 50 mg/kg or 100 mg/kg intraperitoneally. Blood samples were collected at 0, 5, 15, 30, 45 min and 1, 1.5, 2, 4, 8, 12, 24, 48 h after administration. The substrate and its potential metabolites were separated using HPLC on a reverse phase system. 4-Fluorobenzoic acid and one unidentified metabolite were detected together with substrate.
Keywords: Hydrazide hydrazone; In vivo metabolism; Rats